INTERVIEW OF THE EDITOR-IN-CHIEF OF THE JOURNAL “COMPARATIVE POLITICS”, PROFESSOR ALEXEI D. VOSKRESSENSKI’S WITH ANDRANIK MIGRANYAN, DIRECTOR OF THE INSTITUTE FOR DEMOCRACY AND COOPERATION (N.Y., USA) - A. M. Migranian; A. D. Voskressenski (Сравнительная политика)
Abstract: Institute for democracy and cooperation is the first non-profit nonstate organization, set up to become a link between American think tanks and research centers, civil society institutions, universities and Russian intellectual and research centers and political and societal organizations. The IDC director Andranik Migranyan tells about the project of fundamental international research Democracy in the Russian mirror on the basis of the IDC and its significance for the world intellectual community and for Russia, about the project’s American comanager and co-editor Adam Przeworski, on the participants’ selection criteria. Project discussions were held in New York and in Moscow at MGIMO faculty of politics. A. Migranyan evaluates the results of work, the project workshops in Moscow and New York and makes tentative plans for joint follow-up research.